Raman spectrometric discrimination of flexirubin pigments from two genera of Bacteroidetes - Jehlička, Jan; Osterrothová, Kateřina; Oren, Aharon; Edwards, Howell G M (FEMS microbiology letters, 2013)
Flexirubins are specific polyene pigments produced by several genera of Bacteroidetes. Colonies and cell extracts of Flavobacterium johnsoniae and Flexibacter elegans have been investigated by Raman spectroscopy to show that this fast and non-destructive technique can be used to differentiate these pigments from carotenoids and to compare the flexirubin content of the two microorganisms. The presence or absence of certain distinguishing features in the CH combination band region at 2500-2750 cm(-1) can assist in the discrimination between the two flexirubins investigated. Raman spectroscopy is thus a suitable tool not only to detect flexirubin pigments in bacterial cells, but also to further characterize the pigments present in members of the Bacteroidetes genera that are rich in flexirubins.
Keywords: biologické pigmenty; Polyenes; dialkylated resorcinol; identification; polyeny; chemotaxonomy; Pigments, Biological; Bacteroidetes; Spectrum Analysis, Raman; Ramanova spektroskopie; p-hydroxyphenyl group